3-D bone models to improve treatment initiation among patients with osteoporosis: A randomised controlled pilot trial. Issue 4 (2nd April 2016) - Stephens, Melika H.; Grey, Andrew; Fernandez, Justin; Kalluru, Ramanamma; Faasse, Kate; Horne, Anne; Petrie, Keith J.
Abstract : Objective: To investigate the efficacy of 3-D printed bone models as a tool to facilitate initiation of bisphosphonate treatment among individuals who were newly diagnosed with osteoporosis. Design: Fifty eight participants with estimated fracture risk above that at which guidelines recommend pharmacological intervention were randomised to receive either a standard physician interview or an interview augmented by the presentation of 3-D bone models. Main outcome measures: Participants' beliefs about osteoporosis and bisphosphonate treatment, initiation of bisphosphonate therapy assessed at two months using self-report and pharmacy dispensing data. Results: Individuals in the 3-D bone model intervention condition were more emotionally affected by osteoporosis immediately after the interview ( p = .04) and reported a greater understanding of osteoporosis at follow-up ( p = .04), than the control group. While a greater proportion of the intervention group initiated an oral bisphosphonate regimen (alendronate) (52%) in comparison with the control group (21%), the overall initiation of medication for osteoporosis, including infusion (zoledronate), did not differ significantly (intervention group 62%, control group 45%, p = .19). Conclusion: The presentation of 3-D bone models during a medical consultation can modify cognitive and emotional representations relevant to treatment initiation among people with osteoporosis and might facilitate commencement of bisphosphonate treatment.